2014
DOI: 10.1007/s11740-014-0569-4
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of the magnetic abrasive tool for cutting edge preparation of cemented carbide end mills

Abstract: Magnetic abrasive processes combine characteristics of grinding and lapping. Due to deformable tool behavior, complex surface shapes and edges can be machined. Therefore, this process is predestined for preparation of drilled cutting tools. High quality finishing results require in depth process expertise. This paper focuses on the behavior of the magnetic abrasive tool taking Magnetfinish Ò kinematics into account. Main characteristics of the magnetic abrasive tool behavior during finishing end mills of 12 mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Investigation of influence of the MAМ process on the state of microgeometry of details showed that it is appropriate to use at the final stages of production. This method allows the occurrence of combined influence on the state of the surface layer, controllably change its physical and mechanical properties, microgeometry as the working surfaces and the cutting edges of the tool (Baron, 2008;Denkena et al, 2014;Karpuschewski et al, 2009;Maiboroda et al, 2012aMaiboroda et al, ,b, 2017Olt et al, 2018;Payam et al, 2016;Shadab et al, 2017;Tikal, 2009;Wu et al, 2016;Yamaguchi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigation of influence of the MAМ process on the state of microgeometry of details showed that it is appropriate to use at the final stages of production. This method allows the occurrence of combined influence on the state of the surface layer, controllably change its physical and mechanical properties, microgeometry as the working surfaces and the cutting edges of the tool (Baron, 2008;Denkena et al, 2014;Karpuschewski et al, 2009;Maiboroda et al, 2012aMaiboroda et al, ,b, 2017Olt et al, 2018;Payam et al, 2016;Shadab et al, 2017;Tikal, 2009;Wu et al, 2016;Yamaguchi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The geometry of working part of the taps, particularly their cutting edges, has a complex space shape. The modes and conditions of MAM of the taps will be significantly different from the machining modes of other cutting tools (Baron, 2008;Denkena et al, 2014;Karpuschewski et al, 2009;Keksin, 2013;Maiboroda et al, 2012Maiboroda et al, , 2017Maksarov and Keksin, 2018). A great influence on the quality indexes of the tools have features of location of the taps in the working zone of the machine, rotation speed, value of magnetic induction, type and fraction of the magneto-abrasive powder.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to conventional cutting materials, the usage of PCD tools leads to higher chip removal rates and lower tool wear [2]. For some applications, PCD tools have a notable longer tool life than cemented carbide tools [3] or silicon nitride tools [4]. In addition, economical machining of highly abrasive materials is often only possible with PCD tools [5].…”
Section: Introductionmentioning
confidence: 99%